Skeletal Muscle Shape Change in Relation to Varying Force Requirements Across Locomotor Conditions - Konow, Nicolai; Collias, Alexandra; Biewener, Andrew A. (Frontiers in Physiology, 2020)
Contractions of skeletal muscles to generate in vivo movement involve dynamic changes in contractile and elastic tissue strains that likely interact to influence the force and work of a muscle. However, studies of the in vivo dynamics of skeletal muscle and tendon strains remain largely limited to bipedal animals, and rarely cover the broad spectra of movement requirements met by muscles that operate as motors, struts, or brakes across the various gaits that animals commonly use and conditions they encounter. Using high-speed bi-planar fluoromicrometry, we analyze in vivo strains within the rat medial gastrocnemius (MG) across a range of gait and slope conditions. These conditions require changes in muscle force ranging from decline walk (low) to incline gallop (high). Measurements are made from implanted (0.5-0.8 mm) tantalum spheres marking MG mid-belly width, mid-belly thickness, as well as strains of distal fascicles, the muscle belly, and the Achilles tendon. During stance, as the muscle contracts, muscle force increases linearly with respect to gait-slope combinations, and both shortening and lengthening fiber strains increase from approximately 5% to 15% resting length. Contractile change in muscle thickness (thickness strain) decreases (r2 = 0.86; p = 0.001); whereas, the change in muscle width (width strain) increases (r2 = 0.88; p = 0.001) and tendon strain increases (r2 = 0.77; p = 0.015). Our results demonstrate force-dependency of contractile and tendinous tissue strains with compensatory changes in shape for a key locomotor muscle in the hind limb of a small quadruped. These dynamic changes are linked to the ability of a muscle to tune its force and work output as requirements change with locomotor speed and environmental conditions.